2006
DOI: 10.1158/1078-0432.ccr-05-2208
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of the Proto-oncogene Mer in Pediatric T-Cell Acute Lymphoblastic Leukemia

Abstract: Purpose: The Mer receptor tyrosine kinase, cloned from a B-lymphoblastoid library, is the mammalian orthologue of the chicken retroviral oncogene v-eyk and sends antiapoptotic and transforming signals when activated. To determine if Mer expression is ectopic in T-cell acute lymphoblastic leukemia (ALL) and potentially important in leukemogenesis, we analyzed Mer expression in normal human thymocytes and lymphocytes and in pediatric ALL patient samples. Experimental Design: Reverse transcription-PCR, flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 25 publications
0
97
0
Order By: Relevance
“…In addition to the roles discussed in this Review, TAM receptor signalling has been shown have important regulatory roles in vascular smooth-muscle homeostasis [92][93][94] , in platelet function and thrombus stabilization 23,95,96 , in erythropoiesis 97 and in cancer development and progression 19,98,99 . TAM receptors are also implicated in the regulation of osteoclast function 100,101 , in the control of oligodendrocyte cell survival 102,103 , and in the infection of dendritic cells and other cells by Ebola and Marburg viruses 104,105 .…”
Section: Box 1 | Tam Receptor Signalling In Other Tissues and Organsmentioning
confidence: 99%
“…In addition to the roles discussed in this Review, TAM receptor signalling has been shown have important regulatory roles in vascular smooth-muscle homeostasis [92][93][94] , in platelet function and thrombus stabilization 23,95,96 , in erythropoiesis 97 and in cancer development and progression 19,98,99 . TAM receptors are also implicated in the regulation of osteoclast function 100,101 , in the control of oligodendrocyte cell survival 102,103 , and in the infection of dendritic cells and other cells by Ebola and Marburg viruses 104,105 .…”
Section: Box 1 | Tam Receptor Signalling In Other Tissues and Organsmentioning
confidence: 99%
“…However, the pattern differs for each family member, e.g. Mer is found in lymphoid leukemia while Axl is not (Graham et al, , 2006Neubauer et al, 1994).…”
Section: B Expression Patternsmentioning
confidence: 99%
“…Mer is not expressed in normal mouse or human lymphocytes but is ectopically expressed in T-cell leukemias and E2A-PBX1 positive B-cell leukemias (Graham et al, 2006;Yeoh et al, 2002). To further investigate the oncogenic potential and causal role of Mer in malignancy, our lab developed a Mer transgenic (Mer Tg ) mouse model .…”
Section: Cell Survival and Tumor Growthmentioning
confidence: 99%
“…In addition to its role in the clearance of apoptotic cells, as demonstrated in MERTK knockout mice and in individuals with retinitis pigmentosa who display mutations in the MERTK gene, MERTK is overexpressed in several human cancers, including mantle cell lymphoma, gastric cancer, and T-cell acute lymphoblastic leukemia (53)(54)(55)(56). Despite the evidence from MERTK knockout mice and patients with retinitis pigmentosa that MERTK functions as an apoptotic cell removal receptor, in human cancers where MERTK is overexpressed, there appears to be suppressed apoptosis (55,57).…”
Section: Expression Of Mertk On Amsmentioning
confidence: 99%